2013
DOI: 10.1051/0004-6361/201321851
|View full text |Cite
|
Sign up to set email alerts
|

Linear polarization of rapidly rotating ultracool dwarfs

Abstract: Aims. We aim to study the near-infrared linear polarization signal of rapidly rotating ultracool dwarfs with spectral types ranging from M7 through T2 and projected rotational velocities of v sin i 30 km s −1 . These dwarfs are believed to have dusty atmospheres and oblate shapes, which is an appropriate scenario to produce measurable linear polarization of the continuum light. Methods. Linear polarimetric images were collected in the J-band for a sample of 18 fast-rotating ultracool dwarfs, of which five were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 68 publications
7
39
0
Order By: Relevance
“…• 3) at the LIRIS Z, J, H, and K wavelengths (which agrees with the assumption made by Miles-Páez et al 2013), while the angle correction is wavelength-dependent for ALFOSC: from −2.…”
Section: Observations and Data Analysissupporting
confidence: 85%
“…• 3) at the LIRIS Z, J, H, and K wavelengths (which agrees with the assumption made by Miles-Páez et al 2013), while the angle correction is wavelength-dependent for ALFOSC: from −2.…”
Section: Observations and Data Analysissupporting
confidence: 85%
“…following the equations given in Miles-Páez et al (2013) and Wardle & Kronberg (1974). We caution that the expression for the Θ uncertainty is valid for P/σ P ≥ 3, where σ P is the error in linear polarimetry.…”
Section: Discussionmentioning
confidence: 99%
“…A.4), as opposed to the anti-phased g and i light curves discussed by Littlefair et al (2008). The previous J-band (1.2 μm) linear polarimetry measurement by our group (Miles-Páez et al 2013) is also included. It was taken 3.7 months prior to the ALFOSC observations.…”
Section: Light Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend was confirmed by Zapatero Osorio et al (2005) who measured polarization degrees in the range of 0.2-2.5% caused by possible cloud inhomogeneities, rotationally-induced oblateness, or in some cases the presence of a dusty disk or envelope. Near-infrared polarimetry by Miles-Páez et al (2013) showed that the fast rotating dwarfs from their sample (M7 through T2 spectral types) had on average a larger polarization degree than the moderately rotating dwarfs (see also Goldman et al 2009;Tata et al 2009;Zapatero Osorio et al 2011;Miles-Páez et al 2017). Polarimetric observations of self-luminous gas giants and brown dwarf companions are technically more demanding than observations of field dwarfs because of the companion-to-star flux contrast and the small angular separations involved.…”
Section: Introductionmentioning
confidence: 99%